Development of angelonia in pot below doses of slow-release fertilizer - Winhelmann, Mara Cíntia; Emer, Aquélis Armiliato; Tedesco, Marília; Paris, Priscila; Fior, Claudimar Sidnei; Schafer, Gilmar (Ornamental Horticulture, 2018)
Angelonia integerrima is a native species that has ornamental potential, being cultivated in flowerbeds, flowerpots, pots, or even used as a complement in floral arrangements. Knowledge of mineral nutrition is required for the cultivation of the species, and slow release fertilization have become widespread in recent years, with a lower risk of toxicity to crops, an economy in relation to complementary fertilizers and may be an alternative to cultivation of potted plants. The aim of this study was to evaluate the development of Angelonia integerrima Sprengel in pot under slow release fertilization doses. Acclimatized seedlings with approximately 1 cm height, from in vitro germinated seeds were transplanted into 1 L pots containing substrate composted Pinus bark. Five doses of Basacote ® 9M slow release fertilizer, formulation 16-8-12 (N - P2O5 - K2O), 9 months: control - 0 g L-1, 2.5 g L-1, 5.0 g L-1, 7.5 g L-1 and 10.0 g L-1. The plants were grown in a greenhouse under drip irrigation. The shoot length, length of the largest inflorescence, number of stems, diameter of the largest stem, mean length of the stems, number of open flowers, fruits and senescent flowers, chlorophyll a, b and total, mass of dry matter of shoot and root system were evaluated after 286 days. The experimental design was completely randomized, with four replicates of six pots per plot. Data were submitted to analysis of variance (ANOVA) followed by polynomial regression by SigmaPlot 11.0. It was possible to adjust a quadratic equation for the variables: shoot length (with maximum response point in 7.2 g L-1), mean length of stems (6.7 g L-1), diameter of the largest stem and the root system (5.9 g L-1), number of open flowers, buds, senescent flowers and total flowers (7.7 g L-1). For the variables, number of stems, number of fruits, chlorophyll a, b and total did not differ between treatments. The slow releaser fertilizer indicated dose for the cultivation of the potted species is 7.2 g L-1.